On the movement analysis of null subjects in Brazilian Portuguese: Experimental results from extraction of embedded subjects - Claudia Coelho (Universitat Autònoma de Barcelona, 2019)
There is an on-going debate on the empirical adequacy of the movement approach to definite null subjects in Brazilian Portuguese, BP (cf. Ferreira 2000, Rodrigues 2004, and Nunes 2009). On the one hand, Modesto (2000) observes that the null subject of finite embedded clauses associated with object control verbs like convencer ‘to convince’ is subject-oriented, rather than object-oriented and this is unexpected from a movement perspective. On the other hand, Rodrigues (2004) claims that these embedded clauses are actually adjuncts in BP and the observed subject orientation can be accounted for in terms of Hornstein’s (1999, 2001) movement analysis of adjunct control. This paper aims to contribute to this debate by presenting the results of an experiment on grammaticality judgments by BP speakers on the extraction of embedded subjects out of complement and adjunct clauses, as well as finite embedded clauses associated with convencer. The results show that when a distinctive pattern could be observed, finite clauses associated with convencer behaved like adjunct clauses rather than complement clauses. The experiment thus provides confirming evidence for Rodrigues’s (2004) adjunct analysis, invalidating Modesto’s (2000) argument against the movement approach to definite null subjects in BP.